OPTIMISM VALUES IN RACHAEL LIPPINCOTT'S FIVE FEET APART - Ananda, Syafna; Manugeren, M (Universitas Islam Sumatera Utara, 2025)
This study, entitled Protagonist’s Optimism Values in Rachael Lippincott’s Five Feet Apart, aims to analyze the optimism values reflected through the main character, Stella Grant, using a qualitative descriptive method. The analysis focuses on how Stella’s behavior demonstrates optimism as she faces the challenges of living with cystic fibrosis. Despite her illness, Stella remains positive, adheres to her medical treatments, and strives not to burden her parents with grief. Her encounter with Will Newman—a more pessimistic patient—further shapes her understanding of life, resilience, and self-compassion. The study applies Snyder’s framework of optimism as cited in Goleman’s Emotional Intelligence, identifying five core optimism values: having expectations for recovery, persistence, self-motivation, self-confidence, and resilience. The findings reveal that Stella most strongly embodies the values of maintaining high expectations for recovery and demonstrating high self-confidence. These aspects underline the novel’s central message of hope, perseverance, and emotional strength in the face of suffering.